THE EFFECTIVENESS OF SOCIAL ASSISTANCE PROGRAM FOOD ON POVERTY REDUCTION IN INDONESIA - Putri HS Rheviany; Yulianto Tri; Khotimah Nur; Guntur Eko Saputro; Lukman Yudho Prakoso; Sri Murtiana; Agus Winarna; Yudi Sutrasna; Edy Sulistyadi; Juliana Juliana; Gabriel Choirul Alman; Ivan Yulivan; Rianto Rianto (Jurnal Cakrawala Ilmiah, 2022)
In Indonesia, poverty is a very crucial problem, therefore, poverty alleviation must be a top priority in economic development, both in the short and long term. In order to reduce the level of poverty in Indonesia, the Government from 2017 until now has distributed social assistance for basic food programs in 514 regencies/cities throughout Indonesia with different target recipients and aid values ​​each year. The problem of the number of target recipients of social assistance and the value of assistance received by the community is not based on the poverty rate in Indonesia in the 2017-2022 period. This shows that the ineffectiveness of providing social assistance is due to the declining poverty rate, but the value of the assistance provided is increasing. The research approach used is using qualitative research methods using literature studies. This research is aimed at understanding meaning, understanding particular contexts, anticipating unanticipated phenomena and influences, and understanding processes. Based on the results and discussions that can be done in order to increase the Strength of the Social Assistance Program for the Sembako, it is to ensure the fulfillment of the objectives of the program, namely balanced nutrition and preventing stunting. , there are problems related to the aid received by the poor that is not timely, the basic food materials received by the community are not suitable for consumption (low quality). From the Opportunities side of the Social Assistance Program, the Sembako Program is that the basic food assistance program has not become one of the aids that contribute directly to poverty reduction, and the Threats are that there is no regulatory update related to the criteria for the poor, so that the regions have their own criteria, policies have not accommodated special conditions , as well as changes to regulations that change the policy for distributing social assistance programs